STRATEGI KOMUNIKASI PUBLIC RELATIONS SMAN 10 KOTA BOGOR DALAM MEMBANGUN CITRA POSITIF DI AKUN MEDIA SOSIAL INSTAGRAM - Tumpak Panggabean, Yohanes; Suparman; Riyanto, Sutisna; Dharmawan, Leonard; Khairunisa, Anggi Widia; Awalina, Salwa Putri (NIVEDANA : Jurnal Komunikasi dan Bahasa, 2024)
This study delves into the public relations communication strategies implemented by SMAN 10 Kota Bogor through its Instagram account to build a positive image. Guided by the Agenda Setting Theory, the research examines how media influences public perception by highlighting specific issues. The study employs a descriptive qualitative method, with data obtained through in-depth interviews with the public relations team, the principal, and student representatives who follow the school’s Instagram account. The findings reveal that the public relations team utilizes Instagram as the primary platform to share information about academic achievements, extracurricular activities, and other school events. Content is strategically designed to highlight the school’s strengths and foster a positive image. Consistent and creative strategies, including proper scheduling of posts, enhance user engagement. Content formats such as photos and videos effectively capture attention, aligning with Instagram’s visual-centric nature. These strategies successfully establish SMAN 10 Kota Bogor’s branding as an active and accomplished public school. The increasing number of followers, interactions, and inquiries regarding enrollment demonstrate the strategy’s effectiveness. Moreover, SMAN 10 Kota Bogor was recognized as the second- best social media platform in West Java by the Directorate of Senior High School Development, West Java Provincial Education Office. This study underscores the importance of systematic approaches and two-way interactions in building a positive school image on social media.